PERENCANAAN PEMASARAN BERBASIS KOMUNITAS SEKOLAH DALAM MENUMBUHKAN LOYALITAS ORANG TUA - Abeh, Yohanes Andy; Batang, Samson; Wan, Markus; Wibawa, Radhitya; Mebang, Desi Natalia; Fitriadi, Ahmad; Mulawarman, Widyatmike Gede; Komariyah, Laili; Nurlaili, Nurlaili (Penerbit Lafadz Jaya, 2025)
In an era of increasingly competitive schools, educational marketing has become a crucial strategy for attracting and retaining students. This study aims to analyze community-based marketing planning in schools and evaluate its effectiveness in building parental loyalty. The research was conducted using a descriptive qualitative approach in a school in Mahakam Ulu Regency, with data collection techniques including interviews, observations, and documentation. The results indicate that active involvement of the school community—including parents, alumni, and the community—in planning and implementing marketing strategies plays a vital role in increasing trust, a sense of belonging, and parental loyalty towards the educational institution. Strategies used include organizing community events, utilizing parental testimonials, leveraging alumni networks, and digital storytelling through community social media. These findings affirm that community-based marketing not only strengthens the school's image but also creates long-term relationships with parents as educational partners. Recommendations include the importance of fostering collaborative communication with parents, forming an active and inclusive school community, and optimizing the potential of alumni and social media as part of a sustainable promotion strategy.